CfDNA detection for HPV+ squamous cell carcinomas. (April 2021) - Chatfield-Reed, Kate; Roche, Veronique P.; Pan, Quintin
Highlights: HPV is an etiologic factor in anal, cervix, and oropharyngeal cancers. Liquid biopsy to detect HPV cfDNA has been studied for various clinical applications. ddPCR is the platform of choice for HPV cfDNA detection. Harmonization of HPV cfDNA isolation and detection protocols are needed. Abstract: High-risk human papillomavirus (HPV) is an etiologic factor in a spectrum of squamous cell carcinomas including anal, cervical, and oropharyngeal. HPV cell free DNA (cfDNA) is shed from the primary tumor into systemic circulation and can be detected using several platforms including quantitative PCR, digital droplet PCR, or next generation sequencing. Levels of HPV cfDNA at time of initial presentation is associated with known poor prognostic clinicopathologic variables, such as advanced stage and, locoregional and distant metastases. Moreover, longitudinal sampling revealed that persistent or increasing HPV cfDNA levels are indicative of treatment relapse and, in some studies, HPV cfDNA detection predicted treatment failures prior to routine post-treatment clinical imaging. A liquid biopsy platform using HPV cfDNA offers unique advantages over traditional approaches and may have clinical utility for detection of minimum residual disease, treatment response, and disease progression in patients with HPV+ cancers.